(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Reaction of 3-[4-(dimethylamino)phenyl]-(1-methyl/phenyl)prop-2-en-1-one (Chalcones) was carried out with hydrazine hydrate, phenyl hydrazine, isoniazide, nicotinic hydrazide and thiosemicarbezide (corresponding hydrazides) in ethanol containing a few drops of glacial acetic acid under microwave irradiation giving N, N-dimethylaniline containing pyrazole derivatives. The structures of the synthesized compounds were assigned on the basis of elemental analysis, IR and 1H NMR. All the synthesized compounds have been screened for their antibacterial and antifungal activities.